(untitled) (Journal of Medicine, 2018)
Background: Antibiotics Resistance has been in the limelight of medical developments for long. The patient factor, mainly social aspect of it is overshadowed by ever growing new potent drugs and medical technologies. Bangladesh is no exception to the rest of the world. However, relatively fewer works have been published on the relationship between Knowledge, Attitude and Practice (KAP) and Antibiotics Resistance within Bangladesh. This study was done to assess the present status of knowledge, attitude and practice on the use of antibiotics among the people visiting a tertiary care dental hospital in Dhaka; Bangladesh. This will further assess the current status of knowledge on antibiotics and its resistance, attitude towards its use and practices pertaining to it among Bangladeshi general public. It is also aimed at evaluating the behavioral pattern towards use of antibiotics among these group within wide range of income groups and different educational backgrounds. Materials & Methods: A cross-sectional observational study was conducted among patients attending OPD of Dhaka Dental College & Hospital. Patients from all the social background participated in this study. Sample sizes of 562 patients were surveyed. Structured self–administered assessment questionnaire was used to collect the data. SPSS version 24 software was used for data analysis. Results: Of 562 respondents; 64% were female while male constituted 36%. Majority of them fell in the age group of 18-47 consisting of 84.4%. 62.4% of the respondents were married and majority 94% belonged to Muslim faith.93.2% of the respondents had at least primary level educational status. 52% of the respondents belonged to the low income group while 48% constituted high income group. 86.1% of the total respondents knew that indiscriminate use of antibiotics leads to certain harm to the body, while the majority, almost 97.5% have never heard of the term antibiotics resistance. There appears to be statistically significant relationship between the level of education and higher income group with that of KAP on antibiotics usage. Conclusions: The study population had variable understandings on antibiotics and its resistance. This study provides the need to educate people to make them change their mindset towards antibiotics. Most of the people don’t take antibiotics after their infections are subsided or after they become alright. A better and revised strategy of awareness campaign might be needed among the public to educate them on it. J MEDICINE JUL 2018; 19 (2) : 84-90